(untitled) (Iraqi Journal of Medical Sciences, 2019)
Background: Blood preservation and the development of sterile collection sets made possible the developments in blood components preparation, storage and transfusion that we have in today’s blood banks and transfusion services. Objective: To investigate the effects of gamma irradiation, ascorbic acid and the combined effect of both on the lifespan of erythrocytes through determining red blood cells hemolysis for conserving it as long as possible without any change in erythrocytes biophysical properties. Methods: The blood was drawn from 10 healthy (5 males and 5 females) volunteers. Sample has been irradiated using 137Cs source. Different concentrations of ascorbic acid were used as an anti-oxidative agent for erythrocytes in blood suspension samples. A spectrometer was used for recording the data. Results: The results showed that 25% of RBCs hemolysis occurred after irradiation with 5Gy of gamma ray during 5th week of storage time while in un-irradiated sample 33.8% of RBCs hemolysis occurred during the 5th week. 25% of RBCs hemolysis for 10 ?M of ascorbic acid concentration started after 7th week while for control started after 4th week. The minimum rates of RBCs hemolysis observed in the samples which pre-treated with (7 and 10) ?M concentrations of ascorbic acid then irradiated with 1 Gy. Conclusion: The results indicated that irradiation of human blood with a certain doses of gamma ray, treated with small concentration of ascorbic acid or both, the two factors together can protect the blood from hemolysis for a longer time and the minimum rate of red blood cells hemolysis was observed for 10 ?M ascorbic acid concentration then irradiation to 1 Gy of gamma ray. Keywords: Gamma ray, ascorbic acid, blood storage, red blood cells, oxidative damage Citation: Faraj KA, Abdullah SH, Muhammad SF. Effects of different doses of gamma rays and ascorbic acid concentration on human RBCs for conservation purpose. Iraqi JMS. 2019; 17(1): 50-56. doi: 10.22578/IJMS.17.1.8